Assortative mating and digit ratio (2D:4D): A pre-registered empirical study and meta-analysis. (December 2020) - Richards, Gareth; Baron-Cohen, Simon; van Steen, Tommy; Galvin, John
Abstract: Background: It has been hypothesised that the ratio of length between the second and fourth fingers (2D:4D), commonly employed as an indicator of foetal sex hormone exposure, may be positively correlated between heterosexual partners. Aims: As previous evidence has been conflicting, our study aimed to determine whether intra-couple correlations exist for digit ratio variables, and if so, to estimate the size and direction of these effects. Study design: We present a preregistered (osf.io/6jg8p) correlational study and quantitative meta-analysis of the available literature, and attempted to locate further published and unpublished data (i.e. 'grey literature') by contacting n = 248 researchers in the 2D:4D and related fields. Subjects: n = 58 heterosexual dating couples from the UK took part in our empirical study, and the meta-analysis included data from k = 11 samples. Outcome measures: We measured digit ratio for the right hand (R2D:4D), left hand (L2D:4D), and average of both hands (M2D:4D), as well as the right-left-difference (D[R-L] ). Results: We found no evidence of significant positive intra-couple correlations in our own data, but a significant (positive) meta-analytic effect size estimate emerged for R2D:4D ( r = 0.072, p = 0.014). The meta-analytic effects for L2D:4D ( r = 0.043, p = 0.303), M2D:4D ( r = 0.070, p = 0.225), and D[R-L] ( r = 0.028, p = 0.649) were all in the same direction but not statistically significant. However, if the sample from Klimek et al. (2014, 2016) were omitted, meta-analysis would also yield a significant positive correlation for M2D:4D ( r = 0.128, p = 0.001). Conclusions: Although our findings are based on a fairly small range of studies, which themselves provide a relatively small sample of participants, they do imply the intriguing possibility of small effects of positive assortment in relation to characteristics associated with the prenatal hormonal environment. Highlights: Digit ratio (2D:4D) is hypothesised to indicate variation in prenatal sex hormone exposure. Assortative mating may occur in relation to traits influenced by foetal testosterone. A new empirical study ( n = 58 couples) observed no intra-couple correlation for 2D:4D. Meta-analysis shows positive intra-couple correlation for R2D:4D ( r = 0.072, p = 0.014). Intra-couple correlations for L2D:4D, M2D:4D, and D[R-L] were not significant.